Monitoring product quality in clinching process : comparison between univariate and multivariate control charts - Ibrahim Sulong (Institute of Mathematics, Universiti Malaysia Perlis, 2014)
In this dissertation, we investigate the stability of clinching process for assembly of LED Lamps II. Currently, univariate control charts such as X chart and R chart are develop for monitoring process target and process variability. However, the company management under study is highlighting the issue of quality in a clinching process because univariate control charts allow only monitoring one quality characteritic at a time. In multivariate environment, there are more than one quality characteristics to be monitored and those characteristics are correlated.